Complementarity between Audited Financial Reporting and Voluntary Disclosure: The Case of Former Andersen Clients - Frankel, Richard M.; Kalay, Alon; Sadka, Gil; Zou, Yuan (The Accounting Review, 2021)
ABSTRACT Prior literature presents various perspectives on the role of financial reporting. One view is that mandatory periodic reporting disciplines managers and encourages timely voluntary disclosure. We examine this “confirmation hypothesis” using the shock to financial reporting quality experienced by Arthur Andersen clients forced to switch auditors. Consistent with the confirmation hypothesis, we find that former Andersen clients increase disclosure after they change auditors. They increase forecasting frequency and enhance forecasting precision and specificity. We present additional cross-sectional evidence that shows Arthur Andersen clients with larger increases in financial reporting quality increased their disclosure by relatively more, even within the sample of Arthur Andersen clients. We supplement our main findings with a battery of tests to reduce the possibility that alternative shocks and uncertainty drive our results. Our findings support complementarity between financial reporting quality and voluntary disclosures.